2012
DOI: 10.1007/s00227-012-1926-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the ability of a non-indigenous and a native seaweed to induce anti-herbivory defenses

Abstract: Phenotypic plasticity could be a key mechanism of successful species invasion. Few studies, however, have evaluated whether a non-indigenous species induces anti-herbivore defenses after its introduction to new habitats. We tested how a non-indigenous (Mastocarpus stellatus) and a native red seaweed (Chondrus crispus) responded to grazing by a periwinkle (Littorina littorea) and an isopod (Idotea granulosa) in Helgoland, Germany. In the donor region of the Mastocarpus population, that is Iceland, the periwinkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The latter suggests that non-native plants experience less herbivory, because they (a) left their coevolved consumers behind and (b) herbivores in the recipient environment fail to recognize them as a food source. The suggestion that non-native species are less attractive for herbivores than native species has been tested for mesoand macrograzer consumption of marine macroalgae in several laboratory experiments [54][55][56]. Although the outcomes were in the most cases ambiguous, the studies showed that grazers frequently prefer native over nonnative algal species-what was again confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 76%
“…The latter suggests that non-native plants experience less herbivory, because they (a) left their coevolved consumers behind and (b) herbivores in the recipient environment fail to recognize them as a food source. The suggestion that non-native species are less attractive for herbivores than native species has been tested for mesoand macrograzer consumption of marine macroalgae in several laboratory experiments [54][55][56]. Although the outcomes were in the most cases ambiguous, the studies showed that grazers frequently prefer native over nonnative algal species-what was again confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 76%
“…In the last 10 years, the occurrence of induced resistance in temperate brown macroalgae has been well demonstrated (reviewed in Pavia 2007, Jormalainen and. Studies on induced resistance in macroalgae are, however, mostly conducted in the laboratory (e.g., Long et al 2007, Molis et al 2008, Haavisto et al 2010, Yun and Molis 2012, and the link between naturally varying herbivory and induced resistance, documented in several terrestrial plant-herbivore interactions (reviewed in Karban et al 1999), has been explored less in the marine macroalga-herbivore interactions. Earlier studies have correlated the amount of grazing in the field with palatability of algae (e.g., Steinberg 1984, Paul and Fenical 1986, Paul and Van Alstyne 1988 and some have demonstrated induced resistance in natural macroalgae populations as a response to artificial damage mimicking herbivory (Van Alstyne 1988, Yates andPeckol 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Diaz-Pulido et al [ 134 ] showed that the morphology of different species of brown algae ( Padina boergesenii ) was significantly affected not only by herbivory but also by climatic and oceanographic factors, and this suggested that algal response to herbivory could also be a seasonal process [ 135 , 136 , 137 , 138 , 139 ]. Populations from more variable environments are considered to be more plastic [ 140 ], and algal phenotypic plasticity is potentially another pivotal mechanism that enables algae to respond to either fluctuating environments [ 141 ] or species invasion [ 142 ]. According to Fordyce [ 143 ], ecological interactions mediated by phenotypic plasticity, which are typical in nature, depend heavily on the morphological responses of the interacting organisms.…”
Section: At a Glance: Key Defence Strategies Of Marine Macroalgae Aga...mentioning
confidence: 99%